Feeding preference of Nezara viridula (Hemiptera: Pentatomidae) and attractiveness of soybean genotypes - Souza, Efrain de Santana [UNESP] (2013)
Nezara viridula (L.) (Hemiptera: Pentatomidae) is a cosmopolitan insect that causes economic damages to several cultures, in particular soybeans (Glycine max [L.] Merr.) Among the techniques that involve Integrated Pest Management, the resistance of plants is pointed as a tool of great value and can contribute to the reduction of populations of insects. The feeding preferences of adults of southern green stink bug (N. viridula), and the attractiveness of soybean genotypes were evaluated under laboratory conditions to detect the most resistant material against attack from this insect. A choice test, using mature grains and green pods of the genotypes was carried out, in which the number of individuals attracted in different periods was counted. Feeding preference was evaluated in the choice tests using green pods and the number of pricks and the average time spent feeding by pricks were evaluated. In addition, texture and trichome density in the green pods were evaluated. The mature grains of 'TMG 117RR' and 'TMG 121RR' were less attractive to the adults of N. viridula. Regarding the green pods, 'IAC 17' and PI 227687 were less attractive; 'IAC 17' and 'IAC PL1' were less consumed, indicating the feeding non-preference as a resistance mechanism. 'IAC 17', 'TMG-117RR' and PI 227687 presented high levels of trichome density, and in 'IAC 17' this morphological characteristic was considered to be the main resistance factor against N. viridula. These results may be useful for breeding programs that focus on the resistance of soybeans to insects.